(untitled) (Progressive Agriculture, 2021)
Cotton seed oilcake and mustard oilcake are excellent and high quality organic manures enriched with essential nutrient elements. A field experiment was carried out at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during boro season of 2019 to investigate the influence of cotton seed oilcake and mustard oilcake on yield attributes, yield, nutrient content and uptake by rice cv. BRRI dhan29. The experiment was laid out in a Randomized Complete Block Design (RCBD) with four replications and seven treatments viz. T1: control, T2: 100% Recommended Fertilizer Dose (RFD), T3: 50% RFD, T4: 50% nitrogen (N) from RFD + 50% N from cotton seed oilcake, T5: 50% N from RFD + 50% N from mustard oilcake, T6: 50% N from RFD + 25% N from cotton seed oilcake + 25% N from mustard oilcake, T7: 50% N from cotton seed oilcake + 50% N from mustard oilcake. The maximum values of all the yield components viz. plant height, panicle length, number of effective tillers hill-1 and filled grains panicle-1 and yields (grain and straw) were found in treatment T2. The highest content and uptake of nutrients – N, P, K and S were also recorded in T2. The performance of T4 and T2 was statistically similar in producing yield parameters, grain and straw yields, nutrient contents and uptake by rice. Among the integrated approaches, the performance of T4 was the best as it produced the second highest grain yield of 6.24 t ha-1 and straw yield of 8.17 t ha-1 with higher nutritional improvement of rice. Application of cotton seed oilcake compensated up to 50% of chemical fertilizer. Therefore, considering the significance of organic manures and soil health, cotton seed oilcake should be considered for application in association with chemical fertilizers for yield enhancement and nutritional improvement of rice. Progressive Agriculture 31 (3): 144-153, 2020